A Scientometric Analysis of Zakat Literature Published in times of COVID-19 Pandemic - Aam Slamet Rusydiana; Aisyah As-Salafiyah (International Journal of Zakat, 2021)
This bibliometric study investigates the development of trends from various studies on the role of zakat in the COVID-19 pandemic published by journals equipped with a digital-object-identifier. The analysis is focused on descriptions of the characteristics and trends of keywords, authors, journals and citations. The data analyzed were 32 DOI-equipped publications indexed by Google Scholar. The search used to determine the research dataset was last updated on March 16, 2021. The data was then processed and analyzed using the VOSviewer application program to determine the bibliometric mapping of research developments on the role of zakat in the COVID-19 pandemic. The results showed that the visualization of the mapping of research developments in this theme was divided into 4 clusters. Cluster 1 consists of 17 topics, cluster 2 consists of 17 topics, cluster 3 consists of 16 topics and cluster 4 consists of 8 topics. The most popular authors in the results of this bibliometric study are Dzarfan Abdul Kadir, then Margaret Adamek. Then the most popular journals are the Journal of Islamic Accounting and Business Research and the International Conference of Zakat (ICONZ) Proceeding. Most citations are occupied by papers written by Bin-Nashwan (2020)